anonymous
  • anonymous
Let m and n be two positive integers. Show that (36 m+ n)(m+36 n) cannot be a power of 2.
Meta-math
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
LET (36m+n)=2^x AND (m+36n)=2^y THEN, (36m+n)(m+36n)=2^(x+y) AlSO, x and y must me both integers
anonymous
  • anonymous
Now, n=2^x - 36m THEN, m+36n=2^y m+36(2^x-36m)=2^y 36 * 2^x -1295m=2^y
anonymous
  • anonymous
Now, I think I have to prove that y is never a integer

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
2^y=36*2^x-1295m 2^y=2^x(36-1295m/2^x) Now, 2^y must be positive so, (36-1295m/2^x) must be positive... Now let 2^z=36-1295m/2^x HERE z also must be an positive integer..... So, 2^z can be 4,8,16,32 NOW,
anonymous
  • anonymous
36-1295m/2^x= 4, 8, 16, 32 1295m/2^x=32, 28 ,16 ,4 2^x=1295m/32 , 1295m/28 , 1295m/16 , 1295m/4
anonymous
  • anonymous
Now, 2^x=1295m/32 , 1295m/28 , 1295m/16 , 1295m/4 2^x=40.47 m , 46.25m , 80.94m ,323.75m Thus, for no positive integer value of m we will get x a integer value......
anonymous
  • anonymous
Hence, (36 m+ n)(m+36 n) cannot be a power of 2.
anonymous
  • anonymous
I have jumped some step......... I hope I made it clear
anonymous
  • anonymous
@eliassaab
anonymous
  • anonymous
@ganeshie8
anonymous
  • anonymous
for \(m=n\) the statement is true suppose \(m\ge n\) in order for \((36 m+ n)(m+36 n)\) to be a power of \(2\) \[36m+n=2^a\]\[m+36n=2^b\]\[a> b\]\[\frac{36m+n}{m+36n}=2^{a-b}=2^c \ \ \ c\ge 1\]\[m+36n | 36m+n\]\[m+36n|36(m+36n)-(36m+n)=1295n\]since \(\gcd(m+36n \ , \ n)=1\) so \(m+36n\) is a divisor of \(1295\) so \((36 m+ n)(m+36 n)\) is not a power of 2
experimentX
  • experimentX
looks like gcd is very important ... i never liked it.
anonymous
  • anonymous
Here is my proof. Suppose not, let m and n be the smallest such that this product is a power of 2. It is easy to see that m and n are divisible by 2. So m = 2 M and n = 2 N. Since ( 36 (2M) + 2 N)(36(2N)+2 M) is a power of 2,then ( 36 ( M) + N)(36( N+ M) is a power of 2 (contradiction).
anonymous
  • anonymous
Short and Neat :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.